2004
DOI: 10.1136/bmj.328.7438.512
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring to reduce antisocial behaviour in childhood

Abstract: The effects of social interventions need to be examined in real life situations as well as studies Politicians and policy makers are increasingly interested in evidence based decision making. They are under pressure to look to research for solutions to policy problems and justify programmes by reference to the knowledge base. It is tempting for policy makers to grasp any research on seemingly intractable social problems, however slim, in the hope of finding simple solutions. Rolling out national programmes bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 15 publications
0
27
1
Order By: Relevance
“…In summary, although the impact of community-based mentoring on risk factors for delinquency is fairly well established, less is known about the effects of mentoring on delinquency or antisocial behavior (Roberts, Liabo, Lucas, DuBois, & Sheldon, 2004) and the impact of mentoring on justice system-involved youth. Some program evaluations have begun to provide positive results (e.g., AIM, 2004;Barnoski, 2002;Jarjoura, 2003), and there are indications that mentoring services may help improve compliance with communitybased interventions for court-involved youth (Gur & Miller, 2004); however, the existing research on this issue is far from conclusive.…”
Section: Mentoring For Justice System-involved Youthmentioning
confidence: 99%
“…In summary, although the impact of community-based mentoring on risk factors for delinquency is fairly well established, less is known about the effects of mentoring on delinquency or antisocial behavior (Roberts, Liabo, Lucas, DuBois, & Sheldon, 2004) and the impact of mentoring on justice system-involved youth. Some program evaluations have begun to provide positive results (e.g., AIM, 2004;Barnoski, 2002;Jarjoura, 2003), and there are indications that mentoring services may help improve compliance with communitybased interventions for court-involved youth (Gur & Miller, 2004); however, the existing research on this issue is far from conclusive.…”
Section: Mentoring For Justice System-involved Youthmentioning
confidence: 99%
“…The probability of bias with nonrandomised studies is an important point for policy makers, and it has been shown across the social policy field (see e.g. Davies et al ., 2000;Gough, 1993;Macdonald, 1997;Oakley, 2000;Oakley & Fullerton, 1996;Roberts et al ., 2004). Thomas et al .…”
Section: Children and Young People: Systematically Reviewing Health Pmentioning
confidence: 93%
“…The inclusion of these additional studies will help practitioners and policy-makers establish more realistic goals and expectations concerning program scale, intensity, length and outcomes. For now, as unsatisfying as it may sound, the conclusion that ''robust research does indicate benefits from mentoring for some young people, for some programmes, in some circumstances, in relation to some outcomes,'' is probably the closest to a ''bottom line'' on youth mentoring that can be reached (Roberts et al 2004).…”
Section: Jolliffe Andmentioning
confidence: 97%